G22 An observational study of change in oxygenation index (oi) and pao2/fio2 (pf) ratio following administration of methylprednisolone for paediatric acute respiratory distress syndrome (pards). (12th March 2018) - Mitting, RB; Egan, H; Goley, P; Nadel, S
Abstract : Aims: Indiscriminate corticosteroid use in pARDS is likely to be harmful, and the development of a randomised, controlled trial (RCT) may be difficult as corticosteroid exposure is very common. 1 The only existing RCT evidence is involving adult patients, and a recent meta-analysis is suggestive of benefit. 2 We have performed a retrospective observational study of serial OI and PF ratio measurements in a cohort of patients with pARDs and failure to wean from invasive mechanical ventilation at 7 days. All patients were treated with prolonged, low dose methylprednisolone. Method: All patients in a single, general PICU treated with methylprednisolone for pARDS between 01 st January 2011 and 31 st December 2016 were included. OI and PF ratio were calculated daily from admission until weaned from invasive mechanical ventilation. Results: 55 patients. Median age 10 months, 45% female. The majority had a respiratory infection as the trigger for pARDS and 95% had significant co-morbidity. Median duration of methylprednisolone therapy=11 days. Median OI was highest on the day of commencement of methylprednisolone (20, IQR 15–30.5) and was significantly improved on day 4 of treatment (p=0.0021 Wilcoxon test). Median PF ratio was lowest on the day of commencement of steroids (96.5, IQR 63–124) but not significantly improved on day 4 of treatment (p=0.0529 Wilcoxon test). Adverse effects observed included new infections in 40%, hypertension in 9% and hyperglycaemia in 13%. The frequency of these were not different between survivors and non-survivors (p=0.284, 0.644 and 0.1 respectively). Survival to ICU discharge was 69%. Conclusion: This data is limited as it is single centre retrospective analysis. However, the appearance of a temporal association between an improvement in respiratory status and commencement of methylprednisolone is suggestive of a possibility of benefit and should therefore be explored further in an RCT, or a multi-centre, comparative effectiveness study. References: . Yehya N, Servaes S, Thomas NJ, Nadkarnj VM, Srinivasan V. Corticosteroid exposure in pARDs. Intensive Care Med2015September;41(9):1658–66. . Meduri GU, et al . Prolonged glucocorticoid treatment is associated with improved ARDS outcomes: Analysis of individual patients' data from four randomised trials and trial-level meta-analysis of the updated literature. Intensive Care Med2016May;42(5):829–40.